Influence of Prehospital Function and Strength on Outcomes of Critically Ill Older Adults. Issue 3 (11th January 2018) - Files, D. Clark; Neiberg, Rebecca; Rushing, Julia; Morris, Peter E.; Young, Michael P.; Ayonayon, Hilsa; Harris, Tamara; Newman, Anne; Rubin, Susan; Shiroma, Eric; Houston, Denise; Miller, Michael E.; et al.
Abstract : Objectives: To understand the influence of prehospital physical function and strength on clinical outcomes of critically ill older adults. Design: Secondary analysis of prospective cohort study. Setting: Health, Aging and Body Composition (Health ABC) Study. Participants: Of 3, 075 older adult Health ABC participants, we identified 575 (60% white, 61% male, mean age 79) with prehospital function or grip strength measurements within 2 years of an intensive care unit stay. Measurements: The primary analysis evaluated the association between prehospital walk speed and mortality, and secondary analyses focused on associations between function or grip strength and mortality or hospital length of stay. Function and grip strength were analyzed as continuous and categorical predictors. Results: Slower prehospital walk speed was associated with greater risk of 30‐day mortality (for each 0.1 m/s slower, odds ratio = 1.13, 95% confidence interval (CI) = 1.04–1.23, P = .004). Grip strength, chair stands, and balance had weaker, non‐statistically significant associations with 30‐day mortality. Participants with slower prehospital walk speed (hazard ratio (HR) = 0.94, 95% CI = 0.90–0.98, P = .005) and weak grip strength (HR = 0.85, 95% CI = 0.73–0.99, P = .03) were less likely to be discharged from the hospital alive. All function and strength measures were significantly associated with 1‐year mortality. Conclusion: Slow prehospital walk speed was strongly associated with greater 30‐day mortality and longer hospital stay in critically ill older adults, and measures of function and strength were associated with 1‐year mortality. These data add to the accumulating evidence on the relationship between physical function and critical care outcomes.